When Do Ecosystem Services Depend on Rare Species?. (August 2019) - Dee, Laura E.; Cowles, Jane; Isbell, Forest; Pau, Stephanie; Gaines, Steven D.; Reich, Peter B.
Abstract : Conservation aims to preserve species and ecosystem services. If rare species contribute little to ecosystem services, yet are those most in need of preservation, tradeoffs may exist for these contrasting objectives. However, little attention has focused on identifying how, when, and where rare species contribute to ecosystem services and at what scales. Here, we review distinct ways that ecosystem services can positively depend on the presence, abundance, disproportionate contribution or, counterintuitively, the scarcity of rare species. By contrast, ecosystem services are less likely to depend on rare species that do not have a unique role in any service or become abundant enough to contribute substantially. We propose a research agenda to identify when rare species may contribute significantly to services. Highlights: Most species in all ecosystems are rare in some form. Rare species are often assumed to contribute little to ecosystem functioning and services, but evidence has accumulated that rare species can substantially contribute to some ecosystem services in a variety of ways. Rare species can have direct and indirect contributions to ecosystem services through species interactions. Research on functional trait uniqueness could provide new insights into the role of rare species in ecosystem services, yet explicit tests of connections between functional traits and measurable contributions to ecosystem processes and services are still needed. The knowledge of when and to what extent rare species can affect ecosystem services is important for identifying situations in which multiple conservation objectives (protecting biodiversity and providing other ecosystem services) are more or less aligned.